2009
DOI: 10.1097/phm.0b013e3181aeab96
|View full text |Cite
|
Sign up to set email alerts
|

Dysautonomia after Severe Traumatic Brain Injury

Abstract: This study found persistent sympathetic overactivity in response to nociceptive stimuli in dysautonomic subjects (mean, 5 yrs postinjury). This significantly extends the duration over which such sympathetic overactivity has been quantified in this group, contributing to the accumulating empirical evidence that dysautonomic paroxysms result from sympathetic overresponsiveness. Given that sympathetic overactivity has now been observed from day 7 through 5 yrs postinjury, quantitative evaluation of patients for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Changes in the neurotransmitter system, driven by stimuli, highlight the importance of considering the triggering event in pathogenetic research. To summarize, the triggering of paroxysm, a sudden exaggerated response originating in the afferent stimulation of the sympathetic nervous system, is responsible for the core pathophysiological features (38,39).…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the neurotransmitter system, driven by stimuli, highlight the importance of considering the triggering event in pathogenetic research. To summarize, the triggering of paroxysm, a sudden exaggerated response originating in the afferent stimulation of the sympathetic nervous system, is responsible for the core pathophysiological features (38,39).…”
Section: Pathophysiologymentioning
confidence: 99%
“…In TBI patients, negative microbial cultivation of blood, cerebrospinal fluid, airway secretion, or urine provides clues for exclusion. In addition, normal electroencephalograms (EEGs) in PSH patients can help to exclude epilepsy and other nervous system diseases (7,39,63,64). In brief, those examinations could improve the efficiency of diagnosis before the preliminary symptoms and validation have occurred (64).…”
Section: Identification Of Pshmentioning
confidence: 99%
“…demonstrated that changes in heart rate variability associated with nociceptive stimuli accompany the onset of sympathetic storming. [ 5 7 ] Retrospective reviews indicate that those with diffuse axonal injury on imaging studies are at highest risk for developing sympathetic storming. [ 3 14 ] Symptoms are thought to persist for months to years, with one study revealing a mean duration of 5 years post-injury.…”
Section: Pathophysiologymentioning
confidence: 99%
“…[ 3 14 ] Symptoms are thought to persist for months to years, with one study revealing a mean duration of 5 years post-injury. [ 5 ]…”
Section: Pathophysiologymentioning
confidence: 99%
“…The model indicates that there exist inhibitory centers in the brainstem and diencephalon which can suppress the sensitization and amplification of afferent sensory information processed by circuits in the spinal cord. Afferent stimuli from the spinal cord could modulate the balance of the sympathetic and parasympathetic systems by input (such as noxious stimuli) from the environment [17,18]. The change of spinal cord circuits amplifies the mild noxious stimuli.…”
Section: Introductionmentioning
confidence: 99%